Examining How Online Professional Development Impacts Teachers’ Beliefs About Teaching Statistics - Lee, Hollylynne S.; Mojica, Gemma F.; Lovett, Jennifer N. (Online Learning, 2020)
With online learning becoming a more viable option for teachers to develop their expertise, our report shares one such effort focused on improving the teaching of statistics. We share design principles and learning opportunities in an online course developed specifically to serve as a wide-scale online professional development opportunity for educators, thus deemed as a massive open online course for educators (MOOC-Ed). In this report we focus on a subset of 412 participants who identified themselves as classroom teachers. We use multiple data sources, quantitative and qualitative, to characterize changes in teachers’ beliefs and perspectives about statistics and identify triggers in the course that appear to influence teachers’ sense making about issues related to teaching statistics. Implications about specific course experiences that served as triggers for critical reflection and change are discussed.